Learning objectives for formal coach education - a document analysis with regard to the competence discourse - Möhrle, A.; Liebl, S.; Sygusch, R. (Sports Coaching Review, 2025)
Sport coaching frameworks - published by umbrella organisations - highlight competent coaches as the main goal of coach education. These frameworks mainly contain learning objectives that should guide coach education. As the member associations (MAs) of the umbrella organisations usually provide coach education, they have developed sport-specific coach education guidelines. The similarities and differences between the umbrella organisations` frameworks and the MAs` guidelines have not been investigated in any study to date. Therefore, this study analysed all N = 506 learning objectives of the German Olympic Sports Confederation (DOSB) and four of its MAs. It becomes clear that the quality of the wording and the level of demand of the DOSB is significantly higher than that of its MAs. Although the learning objectives of the MAs form the basis for coach education, they are often not specific enough when compared to the DOSB framework to ensure that the main goal is achieved.